Boosted photocatalytic nitrogen fixation by bismuth and oxygen vacancies in Bi2MoO6/BiOBr composite structures. Issue 14 (17th June 2021) - Zhang, Yi; Gu, Shuo; Zhou, Xiaoyu; Gao, Kaiyue; Sun, Kai; Wu, Di; Xia, Jingjing; Wang, Xiufang
Abstract : Bi2 MoO6 /VBi+O –BiOBr composites with surface bismuth and oxygen vacancies were synthesized by an ion-exchange method, and exhibited boosted photocatalytic nitrogen fixation activity. Abstract : Photocatalytic nitrogen fixation performance is mainly hampered by slow carrier transport and inefficient surface reaction, where surface oxygen vacancies have been proved to alleviate these limitations. However, there are a few reports on the introduction of metal vacancies into photocatalysts and the effect of metal vacancies on the N2 photofixing properties. Herein, we injected bismuth vacancies (VBi ) into the surface of BiOBr nanospheres with oxygen vacancies (VO ) via an ion exchange strategy to form hierarchical Bi2 MoO6 /BiOBr composite structures. The intentionally introduced VBi adjust the band structures of VO –BiOBr and act as charge separation centers in coordination with VO, which improves the separation efficiency of electron–hole pairs. The presence of VBi and the Bi2 MoO6 phase enhances the light absorption of the composite materials. Additionally, the hierarchical nanosheet assembly structure facilitates the surface adsorption and activation of N2 on the catalyst. In particular, the optimal defect-rich Bi2 MoO6 /VBi+O –BiOBr exhibits the best photocatalytic ammonia production activity. After two hours, the NH3 yield was 412.18 mol L −1 without any noble metal cocatalyst and sacrificial agent, and was nearly 4 times higher than that of the original VO –BiOBr (96.08 mol L −1 ). This work provides a new inspiration for the design of efficient N2 immobilizing photocatalysts through synergistic metal and oxygen vacancy engineering.